A case of recurrent perianal abscess with fistula-in-ano treated with homoeopathy: A case report - Singh, Lalith; Reddy, Mallesh (Indian Journal of Case Reports, 2020)
Perianal abscess often encountered in clinical practice, has a chance of recurrence and fistula formation if not treated properly. The system of modern medicine treats the condition with incision and drainage. This case report is of a 47-year-old male presenting with pain and swelling in the anal region. The patient was diagnosed by ultrasonography (USG) perineum as a recurrent perianal abscess in the right perianal region, who formed a fistulous tract, but who improved with homeopathic treatment, as documented with serial photographs and USG. It highlighted the scope of successful management without surgical procedures.